MAMPUKAH SUBAK BERTAHAN? STUDI KASUS KETAHANAN SOSIAL KOMUNITAS SUBAK PULAGAN, GIANYAR, BALI - Permana, Yogi Setya (Masyarakat Indonesia, 2018)
Most of literature on Subak studies emphasize on the nature of Subak management system rather than its dynamic respond to contemporary social change. However, this article focuses on how Subak community respond to the rapid social change namely massive tourism industry and water shortage. Based on the case of water dispute between Subak Pulagan and PDAM Gianyar, the author argue that the amplification of cultural and symbolic recognition is an effective strategy for bargaining position in the conflictual relation in order to preserve Subak existence. The research method is case study through fieldwork, interviews, and observation.